Calculo de esfuerzos en placas planas sometidas a flujo turbulento - Paba Barbosa, Julio Cesar (1971)
The objective of this work is the determination of the response of a rough, simply supported, rectangular plate excited by a turbulent boundary layer. A general solution has been found for the displacement response of any randomly excited continuos linear system. The method of solution makes use of the generalized harmonic analysis and series expansions in terms of the set of orthogonal functions associated with the normal modes of vibration of the system. 0n the basis of experimental data of Aupperle and Lambert and of the generalized theory, responses were obtained for the displacement, velocity, bending moments, shear loads and stresses for a rough, simply supported, rectangular plate. The results obtained are discussed and compared with the ones by Strawderman for smooth plates. Finally, some suggestions are made for future research on the subject.